Mode of Entry in China for Green0meter - Lecru, Louis; Pichanič, Mikuláš, 1942-; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis examines the entry strategy for Green0meter, a start-up specialising in Environmental, Social and Corporate Governance (ESG) reporting and consultancy, as it plans to expand into the Chinese market. Founded by CEMS program alumni and backed by KBC Group, this enthusiastic team of professionals wants to extend its reach beyond Central Europe. Their essential service is a user-friendly reporting platform that simplifies handling ESG information, which is growing in importance for businesses worldwide. This study discusses the importance of ESG reporting for small and medium-sized enterprises (SMEs), which will likely become a standard requirement in the future. Therefore, Green0meter will try to take advantage of this shift by entering Asian economies and focusing on China's dynamic market. The thesis will explore practical strategies for market penetration and identify the challenges and opportunities Green0meter may face. The goal is to provide a comprehensive plan that will aid Green0meter in successfully establishing itself in China amidst the increasing emphasis on sustainability.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses